Magnetic, optical, and electron transport properties of n-type CeO2: Small polarons versus Anderson localization MAGNETIC, OPTICAL, and ELECTRON TRANSPORT ... TARAS KOLODIAZHNYI et al. - Kolodiazhnyi, Taras; Charoonsuk, Thitirat; Seo, Yu Seong; Chang, Suyong; Vittayakorn, Naratip; Hwang, Jungseek (My University, 2017)
We report magnetic susceptibility, electrical conductivity and optical absorption of Ce1-xMxO2 where M = Nb,Ta and 0≤x≤0.03. The dc conductivity follows a simple thermally activated Arrhenius-type behavior in the T=70-700 K range with a change in slope at T∗≈155 K. The high-temperature activation energy shows gradual increase from ≈170 to 220 meV as the dopant concentration increases. The activation energy of the low-temperature conductivity shows a broad minimum of ≈77 meV at x≈0.01. Electron transport and localization mechanisms are analyzed in the framework of the Holstein small polaron, Anderson localization, and Jahn-Teller distortion models. The fit to the small polaron mobility is dramatically improved when, instead of the longitudinal phonons, the transverse optical phonons are considered in the phonon-assisted electron transport. This serves as an indirect evidence of a strong 4f1 orbital interaction with the oxygen ligands, similar to the case of PrO2. Based on comparison of the experimental data to the models, it is proposed that the defect-induced random electric fields make the dominant contribution to the electron localization in donor-doped ceria.